Parental Leave Policies and Socio-Economic Gaps in Child Development: Evidence from a Substantial Benefit Reform Using Administrative Data - Mathias Huebener; Daniel Kühnle; C. Katharina Spieß (Institute of Labor Economics (IZA), 2018)
This paper examines the effects of substantial changes in paid parental leave on child development and socio-economic development gaps. We exploit a German reform from 2007 that both expanded paid leave in the first year and removed paid leave in the second year following childbirth. Higher-income households benefited relatively more from the reform than low-income households. We use administrative data from mandatory school entrance examinations containing detailed child development assessments at age six within a difference-in-differences approach. Our precise and robust estimates reveal no effects of the changes in parental leave benefits on child development across various socio-economic groups, and consequently no effects on socio-economic development gaps.
Keywords: J13; J18; J22; J24; 330; parental leave benefit; child development; school readiness; motor skills; language skills; socio-emotional stability